Alarm device for self-tracking of progression during wrist rehabilitation - Ramalingam, Mritha; Chinnavan, Elanchezhian; Nur Syamimi, Jasmi; Goh, Mei Xin; Yuvaneswary, Santhiresegar; Rishikesavan, Ragupathy (PHM Society, 2019)
This study aims to design a device for patients requiring wrist rehabilitation. Wrist injury due to accident, sports accidents, stroke, and prolonged hand immobilization often requires physical therapy for rehabilitation to reduce pain, improve range of motion (ROM), and regain strength and function. Physical therapists use a goniometer to measure ROM. Although the systematic treatment for wrist rehabilitation is physical therapy, current researchers are seeking an alternative and self-educative procedure based on engineering principles. This paper proposes a self-educative assessment and progress tracking design by exploiting an engineering design. This design is aided by a microcontroller, interfaced with sensors and display unit to measure wrist orientation of patients. The sensors measure the ROM of patients. This system uses a buzzer as an alarm tool for the patients during therapy exercises. If the patients have achieved targeted movements, a beeping sound would be produced to notify the patients. Thus, patients will be attentive in the treatment and motivated to proceed with the therapy. Visualization of the ROM through the display unit and alarm signal acts as an educating platform. Prototypes are fabricated and used for actual application with patients. Results showed that the proposed design is effective in self-educating the patients with wrist injuries (p<0.001).